Synthesis and Structure of a Novel Thiacalix[4]arene based Triazine Derivative - Deng, Min; Mu, Lan; Zeng, Xi; Jiang, Xue-Kai; Zhang, Yun-Qian; Yamato, Takehiko (Asian Journal of Chemistry, 2012)
Using thiacalix[4]arene and 1,3-bis-(dichloro-s-triazinyloxy)benzene as a starting materials, a novel thiacalix[4]arene based triazine derivative has been designed and synthesized. This nucleophilic displacement reaction occurred in mild condition. The conformation of 1,3-alternate was confirmed by NMR spectra and X-ray crystal structure analyses. Moreover, it formed a unique p-electron-deficient cavity has the potential to recognize cations and anions.